Pengembangan Media Scrapbook Tentang Penerimaan Diri Bagi Siswa Kelas X SMK Negeri 1 Godean - Tri Wahyuningsih; Nararya Rahadyan Budiyono (Concept: Journal of Social Humanities and Education, 2025)
This research is based on the background of adolescent development starting from the formation of personality or the period where adolescents begin to understand themselves and also others. Self-acceptance is when someone recognizes both their strengths and weaknesses without blaming others, and has a strong drive to continue to develop. The importance of self-acceptance is that an individual's ability to accept themselves is the foundation for individuals to embrace all aspects of their lives, both pleasant and challenging, as part of the process of personal experience. The purpose of the research is to help students understand self-acceptance. The method applied in this study is Research and Development (RnD). This scrapbook media is in the form of non-digital media whose material is in the form of books with creativity and animation so as to attract students' reading interest. In the media scrapbook contains the definition of self-acceptance, aspects of self-acceptance, factors of self-acceptance, the impact of self-acceptance, tips for increasing self-acceptance, and is also equipped with positive affirmations, pearls, and also student activities that contain student sharing and are equipped with short stories related to self- acceptance, in order to reflect and evaluate after conducting services. From the results of the analysis, it can be concluded that the development of scrapbook media, with the results of feasibility evaluation by material experts 97.5%, media experts 82.5%, practitioner experts 92.5% and limited product trials on students 87.5%, can be considered very suitable for use in the field. So that the scrapbook development media about self-acceptance for class X students of SMK Negeri 1 Godean is declared very feasible to use. The benefits of this research produce a variety of media in the implementation of guidance and counseling services. However, there are several recommendations for developing this media, namely the need to develop scrapbook media in digital form by processing scrapbook media online or through an application..